2001
DOI: 10.1055/s-2001-16236
|View full text |Cite
|
Sign up to set email alerts
|

Release of β-Endorphin by Prostaglandin E2 to Lower Plasma Glucose in Streptozotocin-Induced Diabetic Rats

Abstract: In the present study, Wistar rats, which received a streptozotocin injection to induce diabetes (STZ-diabetic rats), a model similar to insulin-dependent diabetes mellitus (IDDM) or type 1 diabetes mellitus, were used to investigate the effect of prostaglandin (PG) E2 on plasma glucose. Intravenous injection of PGE2 produced a dose-dependent lowering of plasma glucose level in fasting STZ-diabetic rats after 60 min. In addition to the blockade of this hypoglycemic effect by guanethidine (a noradrenergic nerve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
11
0

Year Published

2002
2002
2007
2007

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
5
11
0
Order By: Relevance
“…The plasma glucoselowering activity of isoferulic acid was abolished in STZdiabetic rats after bilateral adrenalectomy. Similar to previous reports (Koenig et al, 1986;Cheng et al, 2001a), the basal plasma level of BER in STZ-diabetic rats that received bilateral adrenalectomy was not different from that in shamoperated controls. Moreover, no increase in the plasma BER level was obtained in these adrenalectomized diabetic rats after treatment with isoferulic acid at the effective doses.…”
Section: Discussionsupporting
confidence: 79%
“…The plasma glucoselowering activity of isoferulic acid was abolished in STZdiabetic rats after bilateral adrenalectomy. Similar to previous reports (Koenig et al, 1986;Cheng et al, 2001a), the basal plasma level of BER in STZ-diabetic rats that received bilateral adrenalectomy was not different from that in shamoperated controls. Moreover, no increase in the plasma BER level was obtained in these adrenalectomized diabetic rats after treatment with isoferulic acid at the effective doses.…”
Section: Discussionsupporting
confidence: 79%
“…The basal plasma BER was not significantly different in STZ-diabetic rats that received adrenalectomy as compared with the sham-operated group; these results are consistent with our previous data (18). However, both the decrease in plasma glucose and the increase in plasma BER induced by tetrandrine (1.0 mg/kg) were not observed in STZ-diabetic rats with bilateral adrenalectomy, while these effects persisted in the sham-operated STZ-diabetic rats (Table 2).…”
Section: Resultssupporting
confidence: 92%
“…In fact, plasma glucose-lowering activity is not entirely dependent on insulin regulation; for example, physical exercise is traditionally considered beneficial in the treatment of diabetes (21). In addition, our previous reports (16,18,19,22) indicated that activation of opioid μ-receptors plays a role in the regulation of glucose metabolism during an insulin-deficient state. The physiological actions of endogenous β-endorphins are mediated in part by opioid μ-receptors (23).…”
Section: Discussionmentioning
confidence: 89%
“…Blood samples were then centrifuged at 13,000 rpm for 3 min, and an aliquot (10 μl) of plasma was added to 1.0 ml of Glucose Kit Reagent (Biosystems S.A., Barcelona, Spain) and incubated at 37°C in a water bath (Yamato-BT-25, Tokyo, Japan) for 5 min. The concentration of plasma glucose was then estimated via an analyzer (Biosystems 330, Barcelona, Spain) with samples run in duplicate (Forman et al, 1988;Cheng et al, 2001).…”
Section: Induction Of Diabetes and Plasma Glucose Measurementmentioning
confidence: 99%
“…Bilateral adrenalectomy was performed in Wistar rats as described previously (Cheng et al, 2001) using the dorsal approach under pentobarbital anesthesia (30.0 mg/kg, i.p.). Sham-operated animals served as controls.…”
Section: Adrenalectomized Ratsmentioning
confidence: 99%